Role of Serum Transferrin Receptor in Diagnosing and Differentiating Iron Deficiency Anemia from Anemia of Chronic Disease in Patients with Chronic Kidney Disease (BIRDEM Medical Journal, 2017)
Background: Anemia is common in patients with chronic kidney disease (CKD) and this is generally anemia of chronic disease, but iron deficiency anemia (IDA) is also common. Soluble transferrin receptor (sTfR) is a useful marker for IDA. Present study was undertaken to assess the utility of sTfR as a marker of IDA in selected group of Bangladeshi patients with CKD.Methods: This cross-sectional study was conducted in the Department of Nephrology, BSMMU, Dhaka, Bangladesh from January 2013 to December 2014. Patients with anemia admitted in nephrology department whether on hemodialysis or not and medicine department of BSMMU were taken for study. The study population was further divided into two groups; Group A, patients who are having IDA and Group B, patients with ACD and a control group was also selected. Data were collected by face to face interview and laboratory investigations with a self-administered questionnaire.Results: The mean age of the patients in two study groups were 38.40±13.23 and 34.85±10.52 years respectively and male-female ratio were 0.5:1 and 1:0.5. Mean sTfR level was higher (4.81± 1.64 ?g/ml) in patients with IDA than (2.89±1.40 ?g/ml) in patients with ACD (p